Spatiotemporal vanadium distribution in soils with microbial community dynamics at vanadium smelting site. (October 2020) - Zhang, Han; Zhang, Baogang; Wang, Song; Chen, Junlin; Jiang, Bo; Xing, Yi
Abstract: Whereas the adverse effects of vanadium released from smelting activities on soil microbial ecology have been widely recognized, little is known about spatiotemporal vanadium distribution and microbial community dynamics in typical contaminated sites. This study describes vanadium contents associated with health risk and microbial responses in both topsoil and subsoil during four consecutive seasons around an ongoing-production smelter in Panzhihua, China. Higher levels of vanadium concentration exceeding soil background value in China (82 mg/kg) were found close to the smelter. Vanadium concentrations decreased generally with the increase in distance to the smelter and depth below surface, as soil vanadium pollution is induced mainly by atmospheric deposition of vanadium bearing dust during smelting. Residual fraction was the predominated vanadium form in soils, with pronounced increase in bioavailable vanadium during rainfall period due to frequent drought-rewetting process. Topsoil close to the smelter exhibited significant contamination, inducing high probability of adverse health effects. Spatiotemporal vanadium distribution creates filtering effects on soil microorganisms, promoting metal tolerant genera in topsoil (e.g. Microvirga ) and subsoil (e.g. Bacillus, Geobacter ), which is the key in maintaining the community structure by promoting cooperative relation with other taxa. Our results reveal spatiotemporal vanadium distribution in soils at site scale with potential health risk and microbial responses, which is helpful in identifying severe contamination and implementing bioremediation. Graphical abstract: Image 1 Highlights: Vanadium content increase over seasons but declining along depth and distance. Residual vanadium predominates but bioavailability increases in rainfall periods. Topsoil close to the smelter exhibits high probability of adverse health effects. Vanadium promotes various metal tolerant genera (e.g. Bacillus, Geobacter ) in soil. Abstract : Spatiotemporally distributed vanadium in soils of smelter site poses significant health risks and contributes greatly to shape microbial communities.